Tertiary Students’ Perception of Mobile Legend Game on Vocabulary Mastery - Abdul Gazam Diriadi Perkasa; Nazriani Lubis; Rini Fadhillah Putri; Teguh Satria Amin (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2022)
The phenomenon of mobile legend is quite widespread among tertiary students,because all of this game this game is using English, unique, and everyone interested to play this game. . The purpose of this research was to investigate students' perceptions of mobile legends on vocabulary. A qualitative research method with thematic analysis was applied in this research and the subjects of this research were four students of the Universitas Muslim Nusantara Al-Washliyah. Coming to different departments namely; 2 English students with higher experience in learning English, and 2 non English students with less experience in learning English. Based on the result of interview, there were four themes found, namely; Curiosity,Interaction,Obstacle,Confidence, it is implied that all of the EFL students’ have the same level in the curiosity and confidence theme, therefore all of the EFL students’ had the different level in interaction and obstacle. It turned out that the educational background had an impact on this research.